MANAGEMEN KELELAHAN SAAT PERSALINAN MENGGUNAKAN JUS SEMANGKA - wahyuni, islah (Jurnal Ipteks Terapan, 2018)
The condition of fatigue during labor has received little attention for meditative intervention, so it is important in suppressing the adverse effects of fatigue during labor on the mother and fetus, and preventing the incidence of maternal and fetal mortality and morbidity. The purpose of the study to determine the handling of fatigue using watermelon juice in maternal mothers. Anaerobic fatigue was measured using blood lactic acid values, and Visual Analoque Scale-Fatique (VAS-F) quetioner from 68 respondents were divided into 2 groups: treatment and control group were selected concencutive sampling.  Measurement of blood lactate level was performed 2x at before and after treatment. Data analysis was using univariate and bivariate by dependent T test. The results showed that there were significant differences between lactate levels before and after treatment and control group (.003). The VAS-Fatique analysis resulted  the difference in fatigue experienced stage 1 (.015) and  fatigue experienced 24 hour post partum (.001) is lower treatment group compared with the control group. In conclusion, watermelon juice is effective as fatigue handling in maternal mothers, it is recommended that watermelon juice be given to the mother during normal delivery